Impact of four direct oral anticoagulants on rotational thromboelastometry (ROTEM). (5th October 2017) - Seyve, L.; Richarme, C.; Polack, B.; Marlu, R.
Abstract: Introduction: Rotational Thromboelastometry (ROTEM) is a point of care method used to monitor coagulation during surgery and to guide transfusion strategies in patients presenting with severe bleeding. The aim of our study was to determine the impact of four direct oral anticoagulants (DOACs) on 3 commonly used ROTEM tests. Methods: Whole blood samples from 20 healthy donors were spiked in vitro with apixaban, edoxaban, rivaroxaban or dabigatran at 5 different plasma concentrations (0‐1000 ng/mL). EXTEM, INTEM and FIBTEM tests were systematically performed. Results: There was a linear relationship between the increase in clotting time (CT) and plasma DOAC concentrations in both the EXTEM and INTEM tests. We found that the DOAC concentration required to double EXTEM CT was 1042 ± 225 ng/mL for apixaban, 134 ± 38 ng/mL for edoxaban, 176 ± 26 ng/mL for rivaroxaban and 284 ± 73 ng/mL for dabigatran. INTEM CT was less sensitive than EXTEM CT whatever the anticoagulant. EXTEM CT was above the normal range for 5 of 5 spiked samples when the plasma concentrations were 1000 ng/mL for apixaban, 100 ng/mL for edoxaban, 200 ng/mL for rivaroxaban and 200 ng/mL for dabigatran. Maximum Clot Firmness in EXTEM, INTEM and FIBTEM tests was not affected whatever the DOAC or its concentration. Conclusion: This study found a DOAC dose‐dependent increase in ROTEM CTs. ROTEM tests were only poorly impacted by low levels of edoxaban, rivaroxaban or dabigatran. Apixaban had only a low effect even at high concentrations.